The Table & Swirl Method: A Quick Visualization Methodfor Aspects of Circular Material Streams - Wästerlid, Cecilia; Rahnama, Hossein; Ström, Mikael; Abrahamsson, Lena; Öhrvall Rönnbäck, Anna; Jönsson, Christina (Luleå tekniska universitet, Människa och teknik, 2023)
This document describes the Table & Swirl method, which is a quick visualization method for aspects of circular material streams. Use the method to structure and visualize information to understand and share aspects of material streams in a circular economy. It is a time efficient way to start interesting discussions on any topic related to a circular material stream. The method is built around the Table, a tool to in a structured way gather information and the Swirl, which provides quick visualization. The feedback from our test workshops and end-users were: • ”An eye opener!” • ”First, I thought the model was too simple, then I realized how quickly we got into interesting discussions.” This method was developed in the year 2023 by the Research Institute of Sweden (RISE) and Luleå University of Technology (LTU) in the joint project “Feasibility study: Five circular material streams for batteries“, which was financed by Energimyndigheten, the Swedish Energy Agency. Feasibility study: Five circular material streams for batteries